Human Adipose-Derived Mesenchymal Stem/Stromal Cells Handling Protocols. Lipid Droplets and Proteins Double-Staining - Gojanovich, Aldana D.; Gimenez, María C.; Masone, Diego; Rodriguez, Tania M.; Dewey, Ricardo A.; Delgui, Laura R.; Bustos, Diego M.; Uhart, Marina (Frontiers in Cell and Developmental Biology, 2018)
Human Adipose-derived mesenchymal stem/stromal cells (hASCs) are of great interest because of their potential for therapeutic approaches. The method described here covers every single step necessary for hASCs isolation from subcutaneous abdominal adipose tissue, multicolor phenotyping by flow cytometry, and quantitative determination of adipogenic differentiation status by means of lipid droplets (LDs) accumulation, and Western blot analysis. Moreover, to simultaneously analyze both LDs accumulation and cellular proteins localization by fluorescence microscopy, we combined Oil Red O (ORO) staining with immunofluorescence detection. For LDs quantification we wrote a program for automatic ORO-stained digital image processing implemented in Octave, a freely available software package. Our method is based on the use of the traditional low cost neutral lipids dye ORO, which can be imaged both by bright-field and fluorescence microscopy. The utilization of ORO instead of other more expensive lipid-specific dyes, together with the fact that the whole method has been designed employing cost-effective culture reagents (standard culture medium and serum), makes it affordable for tight-budget research laboratories. These may be replaced, if necessary or desired, by defined xeno-free reagents for clinical research and applications.